GOING CONCERN AUDIT OPINION: THE ROLE OF AUDIT DELAY, OPINION SHOPPING, FINANCIAL DISTRESS, LEVERAGE AND SIZE OF COMPANY - Efrizal Syofyan; Kesi Okta Vianti (Jurnal Akuntansi, 2021)
This Research examines the role of audit delay, opinion shopping, financial distress, leverage, and company size on Going concern (GC) audit opinion. This research is classified as the causality research method. The research population is manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2016 and 2019. We used the purposive sampling method to choose the samples from the population. In the end, we got 124 samples. The data were obtained from www.idx.co.id. and other related websites. The study results show that audit delay, opinion shopping, leverage, and company size do not affect GC opinion. But, financial distress has a positive effect on GC opinion. These results give the knowledge about the factors that affect going concern audit opinion. Auditors as individuals who have independence are expected to be careful in issuing going-concern audit opinions. They should consider the factors that may affect their decision.